Impact of combined moisture buffering capacity of a hemp concrete building envelope and interior objects on the hygrothermal performance in a room. Issue 6 (1st November 2016) - Tran Le, Anh Dung; Maalouf, Chadi; Douzane, Omar; Promis, Geoffrey; Mai, Ton Hoang; Langlet, Thierry
Abstract : In this article, a hygrothermal building model, taking into account the building envelope, indoor heat and moisture sources, indoor environment and moisture buffering capacity of interior objects, is presented and validated with the test cases found in the literature. The model is used to study the impact of hemp concrete and the moisture buffer capacity of the interior elements on the prediction of the hygrothermal comfort in the building. The numerical results show that the use of hemp concrete in buildings can ensure good hygrothermal comfort. Besides, taking into account the effect of moisture buffering of indoor objects increases the building performance. Our results also suggest that neglecting moisture transfer through the envelope increases significantly the predicted percentage of dissatisfied indices and reduces the acceptability of indoor air quality during the occupied period. This study also confirmed that the combined relative humidity-sensitive ventilation system and moisture buffering capacity of building envelope and of interior objects is a very efficient way to reduce the heating energy consumption.